Rode liederenkrans [Bladmuziek]. ([S.l.] : [s.n.])
Deze brochure bevat volgende liederen
Socialistenmarsch
't Is mei
Achturenmarsch
Het kanailje
De rode vaan
Le drapeau rouge
Mariannelied
Banierzang
Nederlands
Partituur
Keywords: partituren